Problematika Evaluasi Pembelajaran Pendidikan Agama Islam di Era Merdeka Belajar - Oktiviana, Nindia; Nastiti, Sekar Arum; Mulyono, Mulyono (JURNAL PAI: Jurnal Kajian Pendidikan Agama Islam, 2024)
Freedom to learn is an educational policy that brings significant changes in the learning process, including in the evaluation of Islamic Religious Education (PAI) learning. Evaluation of PAI learning in the Merdeka era. Learning faces various problems, both in terms of philosophy, concept and implementation. This article aims to examine the problems of PAI learning evaluation in the Independent Learning era. The research method used is literature study with a qualitative approach. The research results show that PAI learning evaluation problems in the Merdeka learning era include: 1) A shift in evaluation philosophy from "measuring" to "improving" the quality of learning; 2) Challenges in developing holistic, authentic evaluation instruments; 3) Difficulty in making assessments in the affective and psychomotor domains; 4) ‎Limited teacher competence in ‎carrying out learning evaluations.‎